Ontology, Epistimologi dan Axiologi dalam Filsafat Ilmu Untuk Pengembangan Teori Manajemen Pendidikan Islam - Sari, Rahmi; Elvarisna, Elvarisna; Marsena, Miftahul; Jamilus, Jamilus (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to determine the role of Ontology, Epistomology and Axiology in the philosophy of science, as well as the basic values in Islamic Education Management. This type of research uses literature study with the stages of Literature Search, Source Evaluation and Selection, Critical Analysis, Theme or Category Grouping, Synthesis of Findings, Identification of Research Gaps, and Writing of Literature Review. The main sources of this research are scientific articles from the results of the research, books, and other sources that are relevant to the main topic of the research. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The findings of this research are the construction of Islamic Education Management Theory based on the integration of Islamic values with modern management concepts. Principles such as monotheism, shura, trust, and justice are important foundations, followed by the application of managerial principles such as planning, organizing, mobilizing, and controlling which are all oriented towards the formation of kamil people. These values of Islamic education management not only focus on technical and administrative aspects, but also uphold moral, spiritual, and social aspects. The implementation of Islamic education management faces a variety of complex challenges, ranging from the difficulty of balancing Islamic values with modern demands, to a lack of understanding and commitment to Islamic principles.